Front Cover: CO(2) Capture with Silylated Ethanolamines and Piperazines (ChemistryOpen 9/2020) - Herbig, Marcus (ChemistryOpen, 2020)
The Front Cover shows the reaction of CO(2) with a silyl derivative of the biogenic amine ethanolamine. The role of CO(2) as a contributor to climate change makes “carbon capture” a desirable goal. However, in addition to simply capture CO(2), aminosilanes form silylcarbamates, which represent starting materials for a variety of crucial chemicals. Thus, the entrapped CO(2) represents a useful C(1) building block. The ESF‐funded Junior Research Group CO(2)‐Sil at the TU Bergakademie Freiberg (represented by their Logo and location) pursues that kind of goals. More information can be found in the Full Paper by Marcus Herbig et al.[Image: see text]